Visum Et Repertum Quality of Sexual Violence Cases in Semarang City - Adzanti, Firdhausyah (Jurnal Forensik dan Medikolegal Indonesia, 2019)
The incidence of sexual violence cases in Indonesia has increased from year to year. In 2015, Semarang was the city with the highest distribution of sexualviolence cases in Central Java. The role of doctors in sexual violence cases is to provide assistance of an examination as well as to collect the evidence from the victim's body then written it in the form of visum et repertum. Good quality of visum et repertum can assist law investigations and law enforcement for the victims. The quality of visum et repertum in Semarang City, represented by two major hospitals in the Semarang named Dr. Kariadi hospital and Dr Adhyatma MPH hospital year 2015-2017. The assesment is using scoring method which developed in previous study by Herkutanto, and then developed for sexual violence cases. The quality of visum et repertum of sexual violence cases measured by scoring of each component (preliminary aspects, aspect of reporting, aspects of conclusions).The percentage of quality from 17 visum et repertum issued by Dr. Kariadi hospital is 84.15%, and the percentage of quality from 60 visum et repertum issued by Dr. Adhyatma MPH hospital is 64.50%. The total percentage of quality of 77 visum et repertum in Semarang is 68.84%, categorized in the medium quality.